Active and reactive power control of three phase grid connected PV system. (2018) - Sahoo, Pradipta Kumar; Ray, Pravat Kumar; Das, Pranati
This paper deals with active and reactive power control of a three phase grid connected photovoltaic system. Maximum power point tracking (MPPT) algorithm is used to track the MPP. The MPPT algorithm uses the IPV and VPV of the PV array and gives the MPP and a Vdc, ref . This voltage is then passed on to the inverter and then further to the three-phase grid. The behaviour of the active and reactive power of the grid which is supplied by the PV array is investigated. The various currents such as inverter current, grid current and load currents are also investigated. MATLAB/simulink has been used to carry out the simulations. The proposed work has also been experimentally verified.